From Friends to Enemies: Negotiating nationalism, tribal identities, and kinship in the fratricidal war of the Malian Tuareg - Georg Klute (L’Année du Maghreb)
The article deals with the notion of friendship in the Tuareg resistance movement. Among Tuareg migrants, friendship terms were mainly used as a political means aiming to strengthen the unity of an imagined, but still utopian Tuareg nation. This changed dramatically in the course of the so called Tuareg rebellion that broke out after thousand of migrants had come back to Mali and Niger from Algerian and Libyan exile in the beginning of the 1990s. Friendship ties which had cut across interethnic and intraethnic boundaries were replaced by ethnic and even tribal identities during the fights. In the context of violent conflicts, like the Tuareg rebellion, friendship bonds which cut across identities of the respective warring parties seem to be rather difficult to maintain. It is argued that friendship is not only a relational term, but a political term as well. In much the same way as kinship, consanguinity, or descent, it may be used to legitimise political relation-building, alliances or hostile relationships.